I Did Not Read "Paco y Lola" - Reyes, Roxana (2002)
Since I reached adulthood, I have been happy that I did not have to use Paco y Lola as a textbook when I learned my first letters. However, that has not exempted me from the gender biases to which girls are subject in the Costa Rican educational system.